Ultrasonography - A boon in dentistry - Abhijeet Alok; Shivani Singh; Mallika Kishore; Anjani Kumar Shukla (Wolters Kluwer Medknow Publications, 2019)
In modern times, advanced diagnostic imaging techniques in oral and maxillofacial radiology mainly involve computed tomography (CT), cone-beam CT (CBCT), magnetic resonance imaging, nuclear medicine, ultrasonography (USG), xeroradiography, and arthrography to name a few. From the time of its discovery, USG has been used in the field of medicine for the diagnosis of lesions as well as for remedial purpose. USG is a technique based on sound waves that acquire image in real time without the use of ionizing radiation. USG is more diagnostic for soft-tissue lesions than hard-tissue lesions. This article reviews the applications of ultrasound imaging in dentistry.